The Impact of Accounting Information Systems and Expense Management on MSMEs Profitability: The Mediating Role of Technological Adaptability and Business Process Digitalization - Ginting, Berupilihen Br; Mahyudin, Mahyudin (Journal Of Accounting Management Business And International Research, 2025)
This study aims to analyze the impact of Accounting Information Systems (AIS) and Cost Management on the profitability of Micro, Small, and Medium Enterprises (MSMEs), with Technology Adaptability and Business Process Digitalization serving as mediating variables. The research was conducted on 275 culinary MSMEs in Medan Marelan Regency using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) method. The findings reveal that AIS significantly influences technology adaptability and profitability, but does not directly affect business process digitalization. Cost Management demonstrates a significant positive effect on technology adaptability, business process digitalization, and profitability. Furthermore, both technology adaptability and business process digitalization significantly affect MSME profitability, although technology adaptability shows a negative impact, suggesting that initial technology adoption may burden profitability due to high investment costs. Indirectly, AIS and Cost Management affect profitability through technology adaptability, while only Cost Management influences profitability through business process digitalization. The study contributes theoretically by enriching the body of knowledge on digital transformation in MSMEs and practically by providing insights for MSME practitioners and policymakers to optimize AIS and cost management in fostering sustainable profitability in the digital era.